Cogeneration in small scale - high speed microturbines dynamic analysis - KICIŃSKI, Jan (Archives of Acoustics, 2010)
Main energy conversion machinery used and to be used in cogeneration systems are schematically described. Some assets of the distributed generation are pointed out and small-scale cogeneration systems designed for energy units of distributed cogeneration are described. In the small scale, turbines and bearings are a source of specific problems connected with securing stable rotor operation. Accepted has been two kinds of high speed micro-turbines of electric power about 3 KW with multistage axial and radial rotors supported on foil bearings. A concept which becomes more and more attractive takes into account a low-boiling agent, which is normally used in the thermal cycle of the micro-turbine, as the lubricating liquid in the bearings (so-called ORC based systems). Of some importance is the operation of these machines at a low noise emission level, sine being parts of the household equipment they could disturb the calm of the residents. The scope of the present article is limited to the discussion of dynamic characteristics of the selected design. The properties of the rotor combined with slide bearings (foil bearings in this particular case) were taken under investigation. A combination of this type is a certain novelty since a typical modal analysis of such objects refers to a rotor itself. Analysing the dynamic state of the "home" power plants requires qualitatively novel research tools.